Digital technologies: Implications for educational organisations and settings in the twenty-first century - Trevor Male (Educational Futures, 2016)
This article investigates the ways in which digital technologies now commonly available and in use can be used to support learning in educational organisations and settings (and change the nature of provision in some instances). A transformation in the attitude and behaviour of teachers, it is argued, is required if the possibilities and opportunities offered by digital technologies are to be maximised now and into the future. In reaching this conclusion the paper examines a number of barriers to change and explores relevant theories of learning that should lead to the situation whereby teachers cannot imagine a world without maximal use of the digital devices that are now available to all learners for whom they have a responsibility.